A Synchrotron and Micro-CT Study of the Human Endolymphatic Duct System: Is Meniere's Disease Caused by an Acute Endolymph Backflow? - Li, Hao; Rajan, Gunesh P.; Shaw, Jeremy; Rohani, Seyed Alireza; Ladak, Hanif M.; Agrawal, Sumit; Rask-Andersen, Helge (Frontiers in Surgery, 2021)
Background: The etiology of Meniere’s disease (MD) and endolymphatic hydrops believed to underlie its symptoms remain unknown. One reason may be the exceptional complexity of the human inner ear, its vulnerability, and surrounding hard bone. The vestibular organ contains an endolymphatic duct system (EDS) bridging the different fluid reservoirs. It may be essential for monitoring hydraulic equilibrium, and a dysregulation may result in distension of the fluid spaces or endolymphatic hydrops. Material and Methods: We studied the EDS using high-resolution synchrotron phase contrast noninvasive imaging (SR-PCI), and micro-computed tomography (micro-CT). Ten fresh human temporal bones underwent SR-PCI. One bone underwent micro-CT after fixation and staining with Lugol’s iodine solution (I2KI) to increase tissue resolution. Data were processed using volume-rendering software to create 3D reconstructions allowing orthogonal sectioning, cropping, and tissue segmentation. Results: Combined imaging techniques with segmentation and tissue modeling demonstrated the 3D anatomy of the human saccule, utricle, endolymphatic duct, and sac together with connecting pathways. The utricular duct (UD) and utriculo-endolymphatic valve (UEV or Bast’s valve) were demonstrated three-dimensionally for the first time. The reunion duct was displayed with micro-CT. It may serve as a safety valve to maintain cochlear endolymph homeostasis under certain conditions. Discussion: The thin reunion duct seems to play a minor role in the exchange of endolymph between the cochlea and vestibule under normal conditions. The saccule wall appears highly flexible, which may explain occult hydrops occasionally preceding symptoms in MD on magnetic resonance imaging (MRI). The design of the UEV and connecting ducts suggests that there is a reciprocal exchange of fluid among the utricle, semicircular canals, and the EDS. Based on the anatomic framework and previous experimental data, we speculate that precipitous vestibular symptoms in MD arise from a sudden increase in endolymph pressure caused by an uncontrolled endolymphatic sac secretion. A rapid rise in UD pressure, mediated along the fairly wide UEV may underlie the acute vertigo attack, refuting the rupture/K+-intoxication theory.